Kuretase Gingiva untuk Manajemen Perawatan Pasien Periodontitis Kronis Localized Stage II Grade A dengan Hipertensi Stage I : Laporan Kasus - Auci Filliandari; Aprilia Yuanita Anwaristi (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction: Periodontitis treatment depends on the severity of the disease, pocket depth, and bone damage. It consists of (1) emergency phase, (2) non-surgical phase, (3) surgical phase, and (4) maintenance or restorative phase. Each phase plays a crucial role in ensuring healing and controlling periodontitis. The non-surgical phase involves scaling and root planing to remove plaque and tartar, while the surgical phase addresses bone damage and pocket reduction. The maintenance phase is critical to preventing disease recurrence. Objective: The purpose of this case report is to demonstrate the success of curettage in a patient with chronic localized periodontitis stage II grade A and stage I hypertension, within a two-week post-treatment period. Case: A 52-year-old female patient presented at RSGM Soelastri with complaints of bleeding gums during tooth brushing. The patient reported gum bleeding around the lower front teeth for the past six months, without any pain. She was regularly taking antihypertensive medication (amlodipine). Examination revealed deep periodontal pockets in teeth 41 and 42, accompanied by gum swelling, indicating chronic localized periodontitis stage II grade A. The patient also had a history of stage I hypertension, which required careful management during treatment. Conclusion: The treatment for chronic localized periodontitis stage II grade A on teeth 41 and 42 with stage I hypertension was curettage. After two weeks of treatment, the patient showed significant improvement, including reduced bleeding and a decrease in pocket depth, with stable hypertension control. Curettage proved effective in managing the condition, with careful consideration of the patient's hypertension risk factors.